2019
DOI: 10.1016/j.invent.2019.100268
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a predictor of treatment adherence and response in an open-access, self-help, internet-delivered cognitive behavior therapy program for child and adolescent anxiety

Abstract: BackgroundAlthough self-help, internet-based cognitive behaviour therapy (ICBT) can produce significant reductions in anxiety for many young people, a sizable proportion show low program adherence and continue to show anxiety problems after treatment. It is important that we identify factors that predict those most likely to complete program sessions and benefit from self-help ICBT so that we can better match interventions to individual needs, and inform program design and development.ObjectiveThis study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
4
25
2
Order By: Relevance
“…For example, Stjerneklar, Hougaard, and Thastum (2019), in a study involving 13‐ to 17‐year‐old anxious youth, found that higher levels of pretreatment anxiety and depression, and female gender were associated with larger reductions in anxiety following iCBT. The degree of parental support in that study was not associated with treatment outcome which differs from Spence, March, and Donovan (2019) who found that greater family support predicted greater reductions in anxiety during an open‐access self‐help iCBT intervention for youth anxiety.…”
Section: Introductioncontrasting
confidence: 89%
“…For example, Stjerneklar, Hougaard, and Thastum (2019), in a study involving 13‐ to 17‐year‐old anxious youth, found that higher levels of pretreatment anxiety and depression, and female gender were associated with larger reductions in anxiety following iCBT. The degree of parental support in that study was not associated with treatment outcome which differs from Spence, March, and Donovan (2019) who found that greater family support predicted greater reductions in anxiety during an open‐access self‐help iCBT intervention for youth anxiety.…”
Section: Introductioncontrasting
confidence: 89%
“…For example, Stjerneklar, Hougaard, and Thastum (2019), in a study involving 13-17 year-old anxious youth, found that higher levels of pre-treatment anxiety and depression, and female gender were associated with larger reductions in anxiety following iCBT. The degree of parental support in that study was not associated with treatment outcome which differs from Spence, March, and Donovan (2019) who found that greater family support predicted greater reductions in anxiety during an open-access self-help iCBT intervention for youth anxiety.…”
Section: Introductioncontrasting
confidence: 85%
“…Moreover, this type of intervention could be employed in different cultures and various contexts, can help to reduce the risk of drop-out and build a strong therapeutic alliance, especially with pre-adolescents and adolescents, and with different conditions such as chronic disease or disability [ 60 , 61 ]. There is also a necessity to create pathways of online support specifically built to target pre-adolescents and adolescents [ 62 , 63 ]. Indeed, this study features a specific limitation due to the loss of a small number of participants (n = 33) who dropped out after the reception interview for various reasons.…”
Section: Discussionmentioning
confidence: 99%